Similar effects of repetitive transcranial magnetic stimulation of MT+ and a dorsomedial extrastriate site including V3A on pattern detection and position discrimination of rotating and radial motion patterns. - Harvey, B; Braddick, O; Cowey, A (2010)
Our recent psychophysical experiments have identified differences in the spatial summation characteristics of pattern detection and position discrimination tasks performed with rotating, expanding, and contracting stimuli. Areas MT and MST are well established to be involved in processing these stimuli. fMRI results have shown retinotopic activation of area V3A depending on the location of the center of radial motion in vision. This suggests the possibility that V3A may be involved in position discrimination tasks with these motion patterns. Here we use repetitive transcranial magnetic stimulation (rTMS) over MT+ and a dorsomedial extrastriate region including V3A to try to distinguish between TMS effects on pattern detection and position discrimination tasks. If V3A were involved in position discrimination, we would expect to see effects on position discrimination tasks, but not pattern detection tasks, with rTMS over this dorsomedial extrastriate region. In fact, we could not dissociate TMS effects on the two tasks, suggesting that they are performed by the same extrastriate area, in MT+.